THE EFFECT OF THE DIFFERENTAMOUNTOF SALT ADDEDIN FERMENTATION OF SHRIMPREBON (Acetes erythraeus) ON THE CONSUMER ACCEPTANCETO CINCALOK - Rosmaniar Rosmaniar; Edison Edison; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study aimed to determine the consumer acceptance on fermented rebon shrimp (cincalok) and the amount of salt appropriate to stimulate the growth of lactic acid bacteria in it.The method used in this research was the experimental method and composed as Completely Randomized Design (CRD).The experiment was conducting byproducingcincalokadded with different amount of salt (15%, 20%, and 25%, each based on the rebon shrimp weight). The parameters used were organoleptic evaluation (appearance, aroma, taste and texture) and the amount oftotal lactic acid bacteria (LAB). The results showed that the different amounts of salt added was significantly affecting to theconsumer acceptance on rebonshrimpcincalok. The highest consumer acceptance of cincalok was produced by addition of 25% salt, showing by the highest value of appearance (7.6), aroma (7.4), flavor (6.4), and texture (6.9).The different amount of salt also affected significantly to the LAB growth, showing by the highest amount of total LAB 17,55 x 103cfu/g in the cincalok produced by addition of 25% salt.It could be concluded that the best treatment was addition of 25% salt to produce the most preferred cincalok. The organoleptic characteristics was shown by the attractive appearance with bright pink color; the rather sour aroma typical of cincalok; a combined taste of slightly acid and salty typical of cincalok; and slightly dense waterytexture.            Key words:Acetes erythraeus, Consumer acceptance, Lactic Acid Bacteria, Salt